Individualized Treatment for Glaucoma Patients with Diabetes mellitus - Luebke, Jan (Klinische Monatsblätter für Augenheilkunde, 2023)
Glaucoma and diabetes mellitus are two common chronic diseases in Europe and worldwide which require intensive therapy. Various pathophysiological mechanisms have been discussed which favour the development of glaucoma, especially in the presence of diabetes mellitus. Medicinal and surgical adjustment of intraocular pressure is associated with some limitations in patients with diabetes mellitus, for example, filtering interventions show lower success rates than in non-diabetic glaucoma patients. Besides pure ophthalmological endocrinological therapy, the psychological burden of two chronic diseases should also be considered and included in the individual therapy plan.
Keywords: glaucoma; diabetes mellitus; chronic disease